Secret empires : how the American political class hides corruption and enriches family and friends - Schweizer, Peter, 1964- (New York : Harper, an imprint of HarperCollinsPublishers, 2018)
"Peter Schweizer has been fighting corruption--and winning--for years. In [past books], he exposed insider trading by members of Congress, ... uncovered how politicians use mafia-like tactics to enrich themselves, ... and revealed the Clintons' massive money machine ... . Now he explains how a new corruption has taken hold, involving larger sums of money than ever before. Stuffing tens of thousands of dollars into a freezer has morphed into multibillion-dollar equity deals done in the dark corners of the world. An American bank opening in China would be prohibited by US law from hiring a slew of family members of top Chinese politicians. However, a Chinese bank opening in America can hire anyone it wants. It can even invite the friends and families of American politicians to invest in can't-lose deals. President Donald Trump's children have made front pages across the world for their dicey transactions. However, the media has barely looked into questionable deals made by those close to Barack Obama, Joe Biden, John Kerry, Mitch McConnell, and lesser-known politicians who have been in the game longer. In many parts of the world, the children of powerful political figures go into business and profit handsomely, not necessarily because they are good at it, but because people want to curry favor with their influential parents. This is a relatively new phenomenon in the United States. But for relatives of some prominent political families, we may already be talking about hundreds of millions of dollars. Deeply researched and packed with shocking revelations, Secret Empires identifies public servants who cannot be trusted and provides a path toward a more accountable government."--Dust jacket.
Corruption by proxy -- American princelings: Two sons and a roommate -- Nuclear and other consequences -- Bidens in Ukraine -- McConnell and Chao: from China with profits -- The princelings of K Street -- The princelings of Chicago -- The Hyesan Youth Copper Mine of North Korea -- Barack Obama's best friend -- More smashing and grabbing -- A real estate mogul goes to Washington -- The Trump princelings.
Includes bibliographical references (pages [229]-300) and index.
Keywords: Political corruption -- United States; Nepotism -- United States; Oligarchy -- United States; Misconduct in office -- United States; United States -- Politics and government -- 21st century; Nonfiction